Member's retention in portuguese fitness clubs: the influence of expectations, positioning, well-being and satisfaction - Gonçalves, Celina (2014)
The objective of this study was to understand how positioning, expectations, well-being and satisfaction influence membership retention in fitness clubs in Portugal. We tried to answer the following question: To what extent do the positioning, perception of the service attributes by the members; the expectations, what is expected from a certain service; the well-being, pleasant being of body and mind; and the satisfaction, contentment of necessities and wishes, influence member retention in fitness clubs.